Metode Story Telling dalam Meningkatkan Motivasi Belajar Sejarah Kebudayaan Islam - Hambali, Hambali; Rozi, Fathor; Hayati, Hayati (AR-RIAYAH: Jurnal Pendidikan Dasar, 2021)
This study aims to analyze and examine the application of the Story Telling method as an effort to increase motivation to learn Islamic Cultural History. The research method used is a descriptive qualitative approach with the type of case study. The research location is in class 5 MI Nurul Mun'im, Paiton District, Probolinggo Regency. Meanwhile, the data collection instruments used in this study included direct observation and unstructured interview notes to support the completeness of the data. Data analysis techniques consist of collecting data, reducing data, presenting data, and then concluding these conclusions. The results obtained from the application of the storytelling method are student learning motivation in following the lesson, students are invited to understand the material in a fun way, namely by telling stories in front of the class. The implication is that students' learning motivation can be achieved by using variations in learning by the teacher so that students do not get bored in class.